2018
DOI: 10.1007/s10566-018-9480-z
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Assets and Academic Performance of Adolescents in Ghana, Kenya, and South Africa

Abstract: Background Overall, youth well-being is crucial, particularly in developmental contexts, such as sub-Saharan Africa, which is experiencing the largest growth in the youth population internationally. The Positive Youth Development (PYD) framework considers the importance of positive experiences, positive relationships and positive environments regarding developmental (further distinguished as internal and external) assets. These assets are important for promoting positive outcomes among youth. Objective The obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Results showed that Ghanaian students reported fewer assets compared to Kenyan and South African students, and across all countries, adolescents with good academic performance reported more developmental assets. Adams et al (2018) observed that students who drew on their internal assets relative to those who did not, were more likely to perform better in school, notwithstanding their country of origin.…”
Section: Overview Of This Special Issuementioning
confidence: 97%
See 1 more Smart Citation
“…Results showed that Ghanaian students reported fewer assets compared to Kenyan and South African students, and across all countries, adolescents with good academic performance reported more developmental assets. Adams et al (2018) observed that students who drew on their internal assets relative to those who did not, were more likely to perform better in school, notwithstanding their country of origin.…”
Section: Overview Of This Special Issuementioning
confidence: 97%
“…The fourth contribution by Adams et al (2018) examined the importance of developmental assets for academic performance in three sub-Saharan African contexts: Ghana, Kenya, and South Africa. In a cross-sectional study, secondary school students in Ghana (n = 428), Kenya (n = 180), and South Africa (n = 184) were asked to complete a survey containing an adapted version of the Benson's (2007) 40 assets as well as provide information on their school grades.…”
Section: Overview Of This Special Issuementioning
confidence: 99%
“…PYD-related research outside the American context has involved samples from, for example, Western Europe Wiium et al, 2018;Gómez-Baya and Benítez-Montagut, 2019), Asia (Chen et al, 2016Chen and Han, 2017), and Africa (Adams et al, 2018). Despite the increasing interest in PYD, contexts, such as Latin American has barely featured in this research.…”
Section: Positive Youth Development and Developmental Assetsmentioning
confidence: 99%
“…Notwithstanding, the optimism that these studies can create, they have been carried out mostly in the USA, and the link between assets and youth outcomes may vary depending on cultural and/or geographical context (Adams et al, 2018;Eichas et al, 2019;Soares et al, 2019). Contexts provide different relevant assets, thus potentially resulting in different outcomes.…”
Section: Developmental Assets Risk Behaviors and Mental Healthmentioning
confidence: 99%
“…Nevertheless, effective PYD programs have been identified mainly in Western contexts, especially among U.S. adolescent samples. Despite a recent growing interest in PYD research in non-Western contexts such as South Africa, Brazil, and Hong Kong (Adams et al, 2019; Schwartz et al, 2017; Zhu & Shek, 2020), validated PYD programs in non-Western contexts are few. With specific reference to mainland China, Shek and Yu (2011) concluded that the number of youth prevention programs was highly inadequate after a review of PYD programs in Asia countries.…”
mentioning
confidence: 99%